Thermal flight performance reveals impact of warming on bumblebee foraging potential - Kenna, Daniel; Pawar, Samraat; Gill, Richard J. (Functional ecology, 2021)
The effects of environmental temperature on components of insect flight determine life‐history traits, fitness, adaptability and, ultimately, organism ecosystem functional roles. Despite the crucial role of flying insects across landscapes, our understanding of how temperature affects insect flight performance remains limited. Many insect pollinators are considered under threat from climatic warming. Quantifying the relationship between temperature and behavioural performance traits allows us to understand where species are operating in respect to their thermal limits, helping predict responses to projected temperature increases and/or erratic weather events. Using a tethered flight mill, we quantify how flight performance of a widespread bumblebee, Bombus terrestris, varies over a temperature range (12–30℃). Given that body mass constrains insect mobility and behaviour, bumblebees represent a useful system to study temperature‐mediated size dependence of flight performance owing to the large intra‐colony variation in worker body size they exhibit. Workers struggled to fly over a few hundred metres at the lowest tested temperature of 12℃; however, flight endurance increased as temperatures rose, peaking around 25℃ after which it declined. Our findings further revealed variation in flight capacity across the workforce, with larger workers flying further, longer, and faster than their smaller nestmates. Body mass was also positively related with the likelihood of flight, although importantly this relationship became stronger as temperatures cooled, such that at 12℃ only the largest workers were successful fliers. Our study thus highlights that colony foraging success under variable thermal environments can be dependent on the body mass distribution of constituent workers, and more broadly suggests smaller‐bodied insects may benefit disproportionately more from warming than larger‐bodied ones in terms of flight performance. By incorporating both flight endurance and likelihood of flight, we calculated a simple metric termed ‘temperature‐mediated foraging potential’ to gain a clearer understanding of how temperature may constrain colony foraging. Of our tested temperatures, 27℃ supported the highest potential, indicating that for much of the range of this species, higher mean daily temperatures as forecasted under climate warming will push colonies closer to their thermal optimum for flight. Subsequently, warming may have positive implications for bumblebee foraging returns and pollination provision. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.